Motivasi Kerja sebagai Pemediasi dari Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Perusahaan Daerah Air Minum (Pdam) Kota Bangkalan - Rahaditya, Reza Rifqy; Aulia Safrizal, Helmi Buyung (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This study discusses the problems found at one of the government institutions, namely the PDAM Bangkalan, East Java. This study aims at determining the effect of work discipline and work environment on employee performance with work motivation as an intervening variable. This study employed a quantitative approach, using path analysis. A total of 51 respondents were involved in this study. The purpose of this study was to examine the effect of work discipline and work environment on employee performance with work motivation as an intervening variable. Based on the results of the analysis, it shows that 1) Work Discipline Variable has a positive and significant effect on Employee Performance. This is shown by the results of the calculation of the t-test, the t- count value is 2.377, and the t-table value is 2.01174 with a significance of 0.022 0.05. 2) Work Environment Variables have a positive and significant effect on Employee Performance. This is shown by the results of the calculation of the t-test, which comprises the t-count value of 2.324 and the t-table value of 2.01174 with a significance value of 0.024 0.05. 3) Work motivation variable has a positive and significant effect on employee performance. This is shown by the results of the calculation of the t-test, the t- count value of 2.212, and the t-table value of 2.01174 with a significance value of 0.032 0.05. 4) The Variable of Work Discipline has a positive and significant effect on Work Motivation. This is shown by the results of the calculation of the t-test, the tcount value of 2.907, and the t-table value of 2.01063 with a significance value of 0.006 0.05. 5) Work Environment Variable has a positive and significant effect on Work Motivation. This is shown by the results of the calculation of the t-test, the tcount value of 3.040, and the t-table value of 2.01063 with a significance value of 0.004 0.05. 6) Work Discipline Variable has a positive and significant effect on Employee Performance through Work Motivation. This is shown by the results of path analysis calculations with a path coefficient of 0.394 with a t-count of 2.619847 ttable of 2.01174. 7) Work Environment Variable has a positive and significant effect on Employee Performance through Work Motivation. This is shown by the results of path analysis calculations with a path coefficient of 0.479 with a t-count of 1.778234 a t-table of 2.01063.